Cece Rios and the queen of brujas - Rivera, Kaela (Rivera, Kaela. Cece Rios (Series), 2024)
When her vicious tía, Catrina, seizes the throne of Devil's Alley and sets her sights on the living world, Cece Rios must do everything in her power to stop the bruja queen from taking control of the four elements.